ANALISIS SISTEM INFORMASI ZAKAT BERDASARKAN PSAK. 109: Studi Kasus pada Baznas Jamber - Su'ud Wahedi; Ainurrozy, Hanifa (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2023)
The zakat information system is an information network system that functions as a medium of responsibility for financial reports. The zakat information system used by BAZNAS Jember has rules that must be obeyed, these rules are wrapped in the Statement of Financial Accounting Standards (PSAK) 109. PSAK. The research method used is qualitative while the type of research used is field case study research. Based on the results of the analysis in this study, it shows that the zakat information system used by BAZNAS Jember is a system that was launched to back up SIMBAZNAS. This SIZ solves the problem of accountants using excel for recording zakat at BAZNAS Jember. The implementation of the Zakat Information system used by BAZNAS Jember has been covered to comply with PSAK. 109 which aim to recognize, measure, present and disclose transactions at BAZNAS.